(untitled) (Південний архів (історичні науки), 2022)
Purpose. The purpose of the study is to identify trends and regularities in the development of international tourism as a factor in the European integration of Ukraine: in historical and modern aspects, to investigate the history of the development of international tourism in the world and in Ukraine, to analyze the problems and prospects of the development of international tourism. The article examines the influence of the historical development of integration processes and globalization transformations in the world on the current state of the tourism industry in Ukraine. Methods. The work uses general scientific methods and techniques of research: analysis, synthesis, comparison, analysis of statistical data. The analysis of the points of view of foreign and domestic authors on international tourism market research made it possible to substantiate the historical aspects of the development of international tourism as a factor in the European integration of Ukraine, as well as to determine the current directions of tourism development in the context of European integration processes in Ukraine. Results. With the help of statistical methods, the dynamics of the main indicators of the tourism industry of the world and Ukraine in the period 2016-2019 and their influence on the effectiveness of the development of this sphere were analyzed, and the prospects of further cooperation between Ukraine and the EU countries in the tourism industry were proven. Based on the statistical data of international organizations: the World Tourism Organization (UNWTO), the World Tourism and Travel Council (WTTC), the United Nations (UN), indicators of international tourist flows were studied, and the main trends in the development of international tourism at the current stage were identified. Conclusions. In the process of research, it was established that European integration, the processes of expansion of which are taking place in the countries of the European Union, has a significant influence on the dynamics of the growth of international tourist flows. The current stage of Ukraine’s economic development is determined by the implementation of international economic policy aimed at the European integration of Ukraine, including ensuring the development of recreational and tourist activities between countries.